STUDENT MANAGEMENT ACTIVITIES AT JUNIOR HIGH SCHOOL: BEFORE, DURING, AND AFTER THE COVID-19 PANDEMIC - Burhan Nudin; Wizarati Awliya; Yushfi Nidaul Khoiri Erisyah Putra; Azza Diyanah; Nilnannisa Alifiyah (MANAGERIA: Jurnal Manajemen Pendidikan Islam, 2022)
Student management must be designed and implemented to achieve a predetermined goal. The implementation of student management needs to be carried out optimally by education personnel for the fulfilment of the rights of students. This study analyzes student and classroom management activities at SMPN 1 Ngemplak Sleman Yogyakarta. This Research is qualitative Research using a descriptive-qualitative approach. The data of this study were obtained from interviews, observations, and documentation. The informants in this research interview were several teachers and students from Junior High School 1 Ngemplak. This Research is located in Junior High School 1 Ngemplak. The research data were tested using data triangulation techniques. This study shows differences in student and classroom management implementation: before, during, and after the COVID-19 pandemic. The performance of student management and classroom management: before, during, and after the COVID-19 pandemic certainly has challenges that require educators to be more creative in student management and classroom management.